Economic development potential through IP telephony for Namibia - Albertus Aochamub; Daniel Motinga; Christoph Stork (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The aim of this study is to evaluate the economic development potential for Namibia through IP telephony. First, background information on the telecommunication sector in Namibia is given. Then, the link between the ICT sector and GDP growth is being investigated. Granger causality tests indicated unilateral causality from GDP growth to telecommunications investment. Due to the small sample size, the causality tests could only be carried out for a lag length of 4, i.e. one year. The analysis might have yielded different result using a larger sample and a longer lag length. The potential impact of IP telephony for Namibia is evaluated using mainly descriptive means due to the lack of data availability. The conclusions drawn from this study are that IP telephony will affect developing countries sooner or later. IP telephony addresses two of the four cost factors of distance. It can make it cheaper to search for trading partners and reduce the cost of managing and monitoring distant production facilities. IP telephony offers the opportunity to improve competitiveness and to attract foreign direct investment, but it also poses the threat of being left behind if opportunities are not seized. In the final analysis, the paper argues that developing countries might be able to gain a comparative advantage by implementing IP telephony sooner rather than later.
Keywords: O10; O30; O40; O55; 330; IP telephony; economic growth; telecommunications; ICT; Granger causality; Namibia; Informationstechnik; Telekommunikation; Telefon; Wirtschaftswachstum; Namibia